Beyond reducing fire hazard: fuel treatment impacts on overstory tree survival. Issue 8 (1st December 2014) - Collins, Brandon M.; Das, Adrian J.; Battles, John J.; Fry, Danny L.; Krasnow, Kevin D.; Stephens, Scott L.
Abstract : Fuel treatment implementation in dry forest types throughout the western United States is likely to increase in pace and scale in response to increasing incidence of large wildfires. While it is clear that properly implemented fuel treatments are effective at reducing hazardous fire potential, there are ancillary ecological effects that can impact forest resilience either positively or negatively depending on the specific elements examined, as well as treatment type, timing, and intensity. In this study, we use overstory tree growth responses, measured seven years after the most common fuel treatments, to estimate forest health. Across the five species analyzed, observed mortality and future vulnerability were consistently low in the mechanical‐only treatment. Fire‐only was similar to the control for all species except Douglas‐fir, while mechanical‐plus‐fire had high observed mortality and future vulnerability for white fir and sugar pine. Given that overstory trees largely dictate the function of forests and services they provide (e.g., wildlife habitat, carbon sequestration, soil stability) these results have implications for understanding longer‐term impacts of common fuel treatments on forest resilience.